1976
DOI: 10.1042/bj1560445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clofibrate on some microsomal hydroxylations involved in the formation and metabolism of bile acids in rat liver

Abstract: 1. The liver microsomal metabolism of [4-14C]cholesterol, endogenous cholesterol, 7 alpha-hydroxy-4-[6 beta-3H]cholesten-3-one, 5-beta-[7 beta-3H]cholestane-3 alpha, 7 alpha-diol and [3H]lithocholic acid was studdied in control and clofibrate (ethyl p-chlorophenoxyisobutyrate)-treated rats. 2. The extent of 7 alpha-hydroxylation of exogenous [414C]cholesterol and endogenous cholesterol, the latter determined with a mass fragmentographic technique, was the same in the two groups of rats. The extent of 12 alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In contrast, some studies in rodents did not show an effect on cholesterol 7␣-hydroxylase on fibrate treatment. 19,21 Recently, divergent data on the effect of PPAR␣ agonists on cholesterol 7␣-hydroxylase transcription in promoter-reporter studies have been described. 22,23 The mechanism of action and the potential role of PPAR␣ in the downregulation of cholesterol 7␣-hydroxylase by fibrates remain to be clarified.…”
mentioning
confidence: 99%
“…In contrast, some studies in rodents did not show an effect on cholesterol 7␣-hydroxylase on fibrate treatment. 19,21 Recently, divergent data on the effect of PPAR␣ agonists on cholesterol 7␣-hydroxylase transcription in promoter-reporter studies have been described. 22,23 The mechanism of action and the potential role of PPAR␣ in the downregulation of cholesterol 7␣-hydroxylase by fibrates remain to be clarified.…”
mentioning
confidence: 99%
“…Sterol 12␣-hydroxylase is highly regulated, and many of the early studies carried out were involved in the regulation of the enzyme activity. Clofibrate treatment increases sterol 12␣-hydroxylase activity and mRNA level in rat liver microsomes (14,15). The enzyme was initially purified from rabbit liver microsomes by Ishida et al in 1992 (16), and the activity was shown to be elevated by several treatments, including starvation and administration of streptozotocin in rat.…”
mentioning
confidence: 99%